Cover Feature: Syntheses and Characterization of a Pair of Isomers of Heteroleptic Bis(Bidentate) Ruthenium(II) Complexes with Two Different Monodentate Ligands (Chem. Eur. J. 72/2019). Issue 72 (12th November 2019) - Toyama, Mari; Takizawa, Takako; Morita, Itaru; Nagao, Noriharu; Kuramochi, Yusuke; Ishida, Hitoshi
Abstract : A pair of isomers of heteroleptic bis(bidentate) ruthenium(II) complexes with two different monodentate ligands, cis ‐[Ru(L)(L')XY] n + (L≠L': bidentate ligands; X≠Y: monodentate ligands), has been synthesized for the first time. trans (Cl, Nbpy )‐[Ru(bpy)Cl(dmso‐ S )(Hdpa)] + (bpy: 2, 2'‐bipyridine; Hdpa: di‐2‐pyridylamine) has a deep red color while the trans (Cl, NHdpa )‐isomer is yellow; these together with the DFT calculations and the CV studies are discussed. More information can be found in the Full Paper by M. Toyama, N. Nagao, H. Ishida et al. on page 16582 .